Enhanced Sensitivity to Angry Voices in People with Features of the Broader Autism Phenotype. - Yap, Valerie M. Z.; McLachlan, Neil M.; Scheffer, Ingrid E.; Wilson, Sarah J. (Journal of Autism & Developmental Disorders, 2018)
The present study examined whether the ability to recognize vocal emotional expressions is negatively related to features of the Broader Autism Phenotype (BAP) in the general population. We assessed 61 typically developing adults on a BAP self-report measure (Broader Autism Phenotype Questionnaire) and a purpose-developed online emotion recognition task for efficient delivery of non-linguistic vocal stimuli corresponding to the six basic emotions. Contrary to expectations, we found that higher self-ratings of rigid BAP traits correlated with better recognition accuracy and higher intensity ratings for angry voices. We interpret this anger-specific association as an advantage for enhanced threat detection in the BAP and discuss this finding in the broader context of personality research and interpersonal theory.